2020
DOI: 10.1016/j.rbmo.2020.05.014
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2: diagnostic and design conundrums in the context of male factor infertility

Abstract: The question of whether SARS-CoV-2 (severe acute respiratory syndrome-related coronavirus-2 [SARS-CoV-2], leading to the COVID-19 infection) can be harboured in the testes and/or semen is currently unanswered. It is essential to understand the limitations of both antibody and real-time PCR tests in interpreting SARS-CoV-2 data in relation to analyses of semen and testicular tissue without appropriate controls. This article critically analyses the evidence so far on this, and the possible implications. The limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Little information existed in the validation of diagnostic tests being utilised. Numerous tests have come onto the market since these studies were reported with differing sensitivities and specificities ( Corman et al, 2020 ; Bahadur et al, 2020 ; Laureano and Riboldi, 2020 ) and its use to derive reassurances on major healthcare implication for mothers, babies and healthcare workers need caution. Single occasion screening is likely to miss potentially infected people ( Viswanathan et al, 2020 ) and clinicians should not rely on unexpected negative results and performing serial tests could overcome an individual test’s limited sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Little information existed in the validation of diagnostic tests being utilised. Numerous tests have come onto the market since these studies were reported with differing sensitivities and specificities ( Corman et al, 2020 ; Bahadur et al, 2020 ; Laureano and Riboldi, 2020 ) and its use to derive reassurances on major healthcare implication for mothers, babies and healthcare workers need caution. Single occasion screening is likely to miss potentially infected people ( Viswanathan et al, 2020 ) and clinicians should not rely on unexpected negative results and performing serial tests could overcome an individual test’s limited sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Little information existed in the validation of diagnostic tests being utilised. Numerous tests have come onto the market since these studies were reported with differing sensitivities and specificities (Corman et al, 2020;Bahadur et al, 2020;Laureano and Riboldi, 2020) potentially infected people (Viswanathan et al, 2020) and clinicians should not rely on unexpected negative results and performing serial tests could overcome an individual test's limited sensitivity. Recent studies though not covered in our analyses are unlikely to alter the findings of this study as concerns about the lack of serial diagnostic analyses remain.…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Although viral RNA can be detected by RT-PCR even after symptoms have disappeared, the amount of viral RNA detected is substantially reduced over time and is generally below the threshold for the virus' ability to replicate. Therefore, it is a safe approach to combine the time between the onset of symptoms and the disappearance of symptoms based on current data [4], [14].…”
Section: Is Sars-cov-2 Transmissible In a Reverse Transcriptase-polymerase Chain Reaction (Rt-pcr) Positive Patients?mentioning
confidence: 99%